Stratigraphy and U–Pb Zircon–Titanite Geochronology of the Aley Carbonatite Complex, Northeastern British Columbia: Evidence for Antler-Aged Orogenesis in the Foreland Belt of the Canadian Cordillera - McLeish, Duncan F.; Johnston, Stephen; Friedman, Richard; Mortensen, James (Geoscience Canada)

(untitled) (The Geological Association of Canada, 2020)
The tectonic significance and age of carbonatite intrusions in the central Foreland Belt of the Canadian Cordillera are poorly constrained. Recent work has demonstrated that one of these carbonatite intrusions, the Aley carbonatite, was emplaced as a syn-kinematic sill, coeval with a major nappe-forming tectonic event. Determining the age of the Aley carbonatite thus provides a means of directly dating syn-tectonic magmatism. Attempts at dating carbonatite units failed due to low U–Pb content in sampled zircon; however, a U–Pb titanite age of 365.9 ± 2.1 Ma was obtained from the Ospika pipe, an ultramafic diatreme spatially and genetically related to the carbonatite. This U–Pb titanite age is further supported by respective 40Ar/39Ar phlogopite ages of 359.4 ± 3.4 Ma and 353.3 ± 3.6 Ma for the pipe and a spatially associated lamprophyre dyke. We interpret the Late Devonian U–Pb titanite age of the Ospikapipe to be the minimum possible age of the carbonatite and syn-magmatic nappe-forming tectonic event. The maximum possible age of the carbonatite is constrained by the Early Devonian age of the Road River Group, the youngest strata intruded by carbonatite dykes and involved in the nappe-forming event. Our dating results for the Aley carbonatite closely correlate with U–Pb zircon and perovskite ages obtained for the Ice River carbonatite complex in the central Foreland Belt of the southern Canadian Cordillera, and support the interpretation of carbonatite intrusions of the western Foreland Belt as genetically linked components of an alkaline-carbonatitic magmatic province. Structural, stratigraphic, and geochronological data from the Aley area indicate that deformation was similar in style to, and coeval with, structures attributable to the Antler orogeny, and are consistent with the Antler orogen having extended the length of the Cordilleran margin from the southern United States to Alaska.